Investigations of Corrosion Resistance of Laser Separated Open Cell Metal1 . Issue 10 (30th May 2017) - Baumann, Robert; Herwig, Patrick; Wetzig, Andreas; Beyer, Eckhard
Abstract : Open cell metal foam contributes promising solutions to the light weight design, battery applications, and renewable energy. Still, challenges are present concerning the cutting into a defined shape. Mechanical processes like milling and grinding create surface smearing on the foam, which leads to a loss of their open cell behavior. Laser remote cutting offers a promising solution in order to overcome those challenges. Their investigations consider that this technique has a high potential concerning cutting speed, which is increased by more than 500% compared to state of the art laser separation techniques. Nevertheless, quality improvements regarding spatter formation and fouling or corrosion resistance has to be investigated. This paper offers insight into the viability of remote laser cutting and how quality aspects can be improved. Abstract : Remote laser cutting offers cut velocities up to 300 m min –1 for open cell metal foam. Note, that the open cell character is still present after machining. In their investigations, salt spray test and alternating climate changing are executed. The laser influences areas exhibit less corrosion behavior. Remote laser cutting shows the best way for sizing open cell metal foams.